The Effect of Allelochemical of Parthenium hysterophorus L., Eucalyptus creba F. Muell., and Casuarina cunninghamiana Miq. on the Germination and Seedling Growth of Lepidium sativum L. - Widia Eka Putri; Endang Sulistyorini; Kirana Nugrahayu Lizansari (Universitas Panji Sakti, 2022)
Allelochemicals are widely known to have antagonistic effects on the environment by inhibiting the physiological activities of other plants. However, this is the whole characteristic of allelochemicals since their effects are not only limited to inhibiting. In low concentration, allelochemicals could have a promoting effect on other plants especially on the germination and seedling stage. This research was conducted to examine the allelochemical activity of Parthenium hysterophorus L., Eucalyptus creba F. Muell., and Casuarina cunninghana Miq. on Lepidium sativum L. with the sandwich method. The leaves of parthenium, eucalyptus, and casuarina were dried and layered between two 5 mL agar in multi well plates and the sterilized seeds of Lepidium sativum L. were set to germinate on the agar. The results showed that the leaves of parthenium, eucalyptus, and casuarina caused lower germination rate compared to the control treatment but led to the greater shoot and root length of Lepidium sativum.